Ritual Dalu Yat sebagai Safety Value Masyarakat Grime Terhadap Wabah Covid 19 - Ruhulessin, Cleopatriza Thonia; Pentury, Marcho David (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Sains dan Teknologi Jayapura, 2020)
This article intends to explain, how ritual of the Dalu Yat became a traditional safety value in the control of Covid 19 plague.A key purpose of the article is the effort to find a knot , that Grime community has a separate mechanism for maintaining balance in its evironment.Interviews and library studies are used to get Data.During this time rituals have always been used to strengthen social relationship, they have also developed as memory in the anticipate of future interactions.However, the article revealed that through ritual Dalu social norms and rules, it was constructed spontaneous and voluntarily, eventually creating a culture of obedience, discipline , and social awareness of protecting the corona virus boundaries. It is a tacit manifestation of local prudence, which shows traditional, adaptive community strength. This article concludes that the ritual Dalu Yat, a culturally specific strategy that separates some activities from certain activities, in order to preserve life, not only in the presebt but also in thr future.